C-peptide: A predictor of cardiovascular mortality in subjects with established atherosclerotic disease. (September 2017) - Cardellini, Marina; Farcomeni, Alessio; Ballanti, Marta; Morelli, Monica; Davato, Francesca; Cardolini, Iris; Grappasonni, Giulia; Rizza, Stefano; Guglielmi, Valeria; Porzio, Ottavia; Pecchioli, Chiara; Menghini, Rossella; et al.
Aim: Insulin resistance and type 2 diabetes are independent risk factors for cardiovascular diseases. Levels of C-peptide are increased in these patients and its role in the atherosclerosis progression was studied in vitro and in vivo over the past years. To evaluate the possible use of C-peptide as cardiovascular biomarkers, we designed an observational study in which we enrolled patients with mono- or poly-vascular atherosclerotic disease. Methods: We recruited 431 patients with stable atherosclerosis and performed a yearly follow-up to estimate the cardiovascular and total mortality and cardiovascular events. Results: We performed a mean follow-up of 56 months on 268 patients. A multivariate Cox analysis showed that C-peptide significantly increased the risk of cardiovascular mortality [Hazard Ratio: 1.29 (95% confidence interval: 1.02−1.65, p < 0.03513)] after adjustment for age, sex, diabetes treatment, estimated glomerular filtration rate and known diabetes status. Furthermore, levels of C-peptide were significantly correlated with metabolic parameters and atherogenic factors. Conclusion: C-peptide was associated with cardiovascular mortality independently of known diabetes status in a cohort of patients with chronic atherosclerotic disease. Future studies using C-peptide into a reclassification approach might be undertaken to consider its potential as a cardiovascular disease biomarker.